Juegos lúdicos y desarrollo psicomotriz en niños de cuatro años de la institución educativa inicial N° 756 del distrito de Iquitos 2024 - Curitima Maricahua, Celvy Kory (2025)
The main objective of this study was to link recreational play and psychomotor development in four-year-old children at I.E.I. 756 in the Iquitos district during the 2024 school year. This study used a quantitative, relational, non-experimental, cross-sectional, and correlational methodology. The sample consisted of 70 parents/guardians, who were administered two questionnaires to gather relevant information. The inferential Spearman correlation coefficient showed a correlation coefficient of 0.935 with a p-value of 0.000, confirming a very positive relationship between recreational play and psychomotor development.